PERLINDUNGAN HUKUM TERHADAP HAK HAK TERSANGKA DALAM SISTEM PENYIDIKAN BERKEADILAN BERBASIS HAK ASASI MANUSIA - Nurwati; Husna, Lenny (SCIENTIA JOURNAL, 2025)
This research discusses the legal protection of the rights of suspects in the investigation process based on human rights principles. The main issue discussed is how the implementation of legal protection of the rights of suspects in Indonesia, including the obstacles faced in practice. The purpose of this study is to evaluate the extent to which existing regulations, such as KUHAP, Law No. 39/1999 on Human Rights, and the International Covenant on Civil and Political Rights (ICCPR), can protect the rights of suspects, as well as to identify obstacles in their implementation. This research uses normative legal methods with legislative, conceptual, and analytical approaches. The results show that although existing regulations have provided a strong legal foundation, violations such as torture, discrimination, and lack of access to legal aid still occur frequently. In addition, weak oversight and limited resources exacerbate the protection of suspects' rights. Therefore, reforms are needed in the aspects of legal implementation, strengthening supervision, and expanding access to legal aid to realize a fair investigation that respects human rights.